The association between sociodemographic factors and depression with quality of life among the elderly survivors of the 2014 flood in Kuala Krai, Kelantan - Ismail, Nurul Nadia (2017)
Backgrounds: Flood results in massive community destruction hence, reduced the physical and psychological status especially among the elderly. However, study on quality of life (QoL) after a disaster among the local elderly population is still lacking. The aim of this study is to determine the association between sociodemographic factors and depression with QOL among these elderly. Methods: This is a cross sectional study conducted six months following flood in 2014. Based on the information District Office (DO) of Kuala Krai, the areas were stratified into six highly populated areas. Three of these areas would give adequate subjects to meet the sample size. The three areas were randomly selected by picking three out of six named areas in an individually enclosed envelops. A total of 156 elderly were selected in this study. Depression was measured using the Malay validated Geriatric Depression Scale (M-GDS15) while QoL was assessed using the WHO Quality of Life questionnaire (WHOQOL- BREF). Results: Proportion of clinically significant depression was 41.29%. Depression showed significant linear negative relationship with physical (-1.83, 95% CI: -2.51, -1.15, p< 0.001), psychological (-1.74, 95% CI: -2.36, -1.12, p< 0.001) and environment domains of QoL (- 0.85, 95% CI: -1.53, -0.16, p= 0.016). Only duration of involvement with flood showed a significant linear negative relationship with all domains. Employment status, previous experience with flood and being married showed significant linear positive relationship.Older old, family history with psychiatry illness and witnessed traumatic event showed significant linear negative relationship with QoL. Conclusion: Proportion for depression in this study was higher in comparison to previous study. Our study confirmed duration of flood and depression have inversed relationship with QoL. This indicated an urgent need for screening program among the elderly for depressive symptoms in the aftermath of disaster. Being older old, having positive family history with psychiatric illness and witnessed traumatic event during the disaster were the risk factors for poorer QoL. This study would improve the management and current policy during disaster.